Regulating The Metaverse: Sharia Compliance, Digital Assets, And The Evolution Of Islamic Economic Law In Indonesia - Muhammad Iman Kurniawan; Mohamad Gally Tawakal; Dewi Sri Astuti; Ahsanul Mufid (Muwafaqat: Journal of Islamic Law, 2026)
Purpose of the study: This study aims to identify doctrinal, regulatory, and institutional gaps hindering Sharia-compliant metaverse governance in Indonesia and to propose an integrative framework based on maqasid al-shariah for digital-asset oversight post-OJK transfer. Methodology: This study employs a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. It synthesizes 42 publications indexed in Scopus and SINTA (2015–2025) using thematic analysis. No software or surveys were applied; the review relies on qualitative document synthesis of peer-reviewed articles and regulatory texts. Main Findings: Three persistent tensions are identified: doctrinal ambiguity on virtual assets' legal status (mal), fragmented multi-regulator governance, and limited DSN-MUI fatwa responsiveness to virtual transactions. These gaps obstruct Sharia-compliant metaverse development, necessitating a tripartite framework integrating fiqh muamalah, prudential regulation, and Sharia-by-design technology. Novelty/Originality: This study offers the first systematic integration of maqasid al-shariah with post-transfer Indonesian digital-asset governance, bridging fiqh muamalah, prudential regulation, and technology design. It advances Islamic economic law by presenting a concrete, context-specific framework for metaverse compliance, addressing regulatory fragmentation and doctrinal uncertainty uniquely.